Male and female songs propagation in a duetting tropical bird species in its preferred and secondary habitat - Amie Wheeldon; Katarzyna Kwiatkowska; Paweł Szymański; Tomasz S. Osiejuk (PLoS ONE, 2022)
Acoustic signals produced by animals must transmit through the environment to reach potential receivers and change their behaviour. Both the environment (vegetation, air properties, other animals) and the form of the signal affect the propagation process. Here we investigated how the transmission of different song types of a duetting songbird species inhabiting an extreme environment within African montane forest, varies between males and females as well as different types of micro-habitats. We hypothesised that male and female songs would have different transmission properties, reflecting known differences in signal form and function. We analysed signal-to-noise ratio (SNR), excess attenuation (EA) and tail-to-signal ratio (TSR) of songs of male and female Yellow-breasted Boubous (Laniarius atroflavus) that were played and re-recorded in a range of sites representing the species-typical habitats. We found significant effects of distance, site (habitat) and sex reflected in all three measures of sound degradation. The clearest, primarily distance-dependent pattern was found for SNR of songs propagated in level forest site. EA was substantially higher in shrubs than in forest habitats, while TSR reflecting longer echoes appeared at longer distances in forest sites. Thus, Yellow-breasted Boubou songs are better propagated in forests than in disturbed sites covered with shrubs. We found that all male song types used for broadcast singing propagated farther than female songs, with significantly higher SNR at all distances. The different male song types which are known to have different functions, also demonstrated a differentiated pattern of propagation reflecting their functionality. All signals that were tested propagated the furthest in the ideal condition described as forest with a level terrain. Signals degraded much faster during transmission through shrubs regrowing after forest burning. On this site, the differences in the propagation of male and female songs, as well as the differences between male song types, were relatively least pronounced. Transmission in typical mountain forest among streams and with substantial terrain variation revealed that degradation pattern in such habitat could be perturbed in a non-linear way. Streams acting as a source of high noise level also negatively affected transmission and may strongly limit the perception of birds staying close to them. However, stream noise did not affect sex differences in song propagation as was found for the site located in shrubs. Male songs showed more efficient transmission through all habitats (least in the shrubs) than female song. These differences were the result of male songs having a whistle structure that is better adapted for long-range propagation than the atonal, wideband frequency female vocalisations. Results support the idea that signals of males of the Yellow-breasted Boubous evolved under the pressure of long-range communication both with rivals and females, while females of the species are much more focused on within-pair communication or signalling together with their partner. The consequence of deforestation resulting in pushing back territories to the forest remnants along streams may be a shortening of the song’s active range, in particular, in females.